Development of mathematical model of linear alkylbenzenes sulphonation film reactor; Chemical Reactors (CHEMREACTOR-22) - Dolganova I. O. Irena Olegovna; Dolganov I. M. Igor Mikhailovich; Ivashkina E. N. Elena Nikolaevna; Ivanchina E. D. Emilia Dmitrievna (2016, 2016)
Title screen